DEVELOPING STUDENTS’ CREATIVE INDEPENDENCE THROUGH QUICK SKETCHING EXERCISES (Western European Journal of Medicine and Medical Science, 2025)
This article examines the role and importance of quick sketch exercises in developing students’ creative independence. During quick drawing practice, students not only enhance their observation, imagination, and artistic thinking, but also develop the ability to make independent creative decisions. The aim of the study is to analyze the methodological foundations for fostering creative independence through quick sketch exercises. The research applied pedagogical observation, comparison, and experimental training methods. Experimental sessions with students of the “Fine Arts and Engineering Graphics” program at Shahrisabz State Pedagogical Institute confirmed the effectiveness of the proposed methodology. The results demonstrated an increase in students’ independent thinking, freedom in image creation, and confidence in drawing techniques. The article is devoted to a comprehensive study of methodology for developing creative independence in art education.